2015
DOI: 10.2174/1567205012666141218144035
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Alzheimer’s Disease and Blood Homocysteine, Vitamin B<sub>12</sub>, and Folate: A Case-Control Study

Abstract: Vitamin B12 was directly associated with AD. The combination of high Hcy, low vitamin B12, and any folate level represented the poorest association with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 34 publications
3
34
1
1
Order By: Relevance
“… 53 Vitamin B 12 deficiency is associated with cognitive impairment, and the level of circulating vitamin B 12 has been associated with AD risk. 54 ABCD4 encodes an adenosine triphosphate–binding cassette transporter that is in the same family as well-established AD gene ABCA7 . 39 , 40 The AD-associated CELSR1 rs61741871 (P2983A) missense variant has also been associated with craniorachischisis, which is a severe neural tube defect, 55 and other CELSR1 variants have been identified as ischemic stroke risk factors in Japanese individuals.…”
Section: Discussionmentioning
confidence: 99%
“… 53 Vitamin B 12 deficiency is associated with cognitive impairment, and the level of circulating vitamin B 12 has been associated with AD risk. 54 ABCD4 encodes an adenosine triphosphate–binding cassette transporter that is in the same family as well-established AD gene ABCA7 . 39 , 40 The AD-associated CELSR1 rs61741871 (P2983A) missense variant has also been associated with craniorachischisis, which is a severe neural tube defect, 55 and other CELSR1 variants have been identified as ischemic stroke risk factors in Japanese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the confounding influence of homocysteine was only adjusted for in a few of the included studies [19,28]. Excessive homocysteine increases the risk of endothelial dysfunction and increases the cardiovascular risk, which directly contributes to the development of dementia and AD by promoting neurodegenerative changes [45]. Therefore, failure to adjust for this confounding factor may result in biased conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…High serum Hcy content, caused by deficiency of B vitamins has been reported to be associated with the risk of AD in population based studies [25,26,27,28]. Gorgone and coworkers found that hyperhomocysteinemia damaged cognitive function via micro-vascular damage and direct neuro-toxic effect [29].…”
Section: Discussionmentioning
confidence: 99%